URGENSI PENERAPAN CALESTIAL MANAGEMENT BAGI PENINGKATAN KUALITAS SDM PADA IKNB SYARIAH - Trimulato, Trimulato (Jurnal Ekonomi Islam, 2016)
Non-bank Islamic financial industry (IKNB Sharia) in Indonesia continues to increase very good. Visible IKNB growth seen in the number of Islamic sharia IKNB assets in 2010, 9333 billion rupiah in the year rose to 46 895 billion rupiah. With an average growth rate of 62.29%. Thus the development of sharia IKNB must be balanced with sufficient resources and qualified. OJK has made  efforts  in  improving  the  quality  of  human  resources  in  Islamic  IKNB  with  two  major strategies. This research uses descriptive qualitative limitations in this paper focused on the OJK in improving the human resources that exist IKNB Shariah. The need for the application of celestial management for human resources in IKNB sharia. The results of this paper that the OJK has set two strategies in an effort to improve the quality of human resources in IKNB sharia. Then the need for the application of celestial management for human resources in IKNB sharia to create good quality. Because IKNB sharia is a business institution that is inseparable from the rule of religion or spiritual aspect. Thus requiring an appropriate concept in improving the quality of its human resources.